The Risks of Using Artificial Intelligence on Privacy and Human Rights: Unifying Global Standards - Al-Billeh, Tareq; Hmaidan, Ruba; Al-Hammouri, Ali; AL Makhmari, Mohammed (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2024)
Artificial intelligence (AI) presents significant opportunities and challenges, particularly balancing innovation with protecting privacy and human rights. The increasing integration of AI into daily life has amplified risks to digital privacy, access to information, and online communication, raising concerns about human rights violations. Governments must address these risks by implementing practical measures to ensure safe AI usage and redressing harm caused by unethical practices. This article explores the impact of AI on privacy and human rights, utilizing the 2024 Council of Europe Framework Convention on AI, Human Rights, Democracy, and the Rule of Law as a basis for ethical considerations. Employing an analytical methodology, the study examines international charters and national legislation to highlight disparities in addressing AI-related privacy concerns and to identify gaps between global human rights standards and digital technologies. Comparative analysis is conducted to evaluate international and national approaches to AI governance. The findings emphasize the urgent need for unified global standards to protect digital human rights, harmonize AI ethics, and reduce risks associated with AI applications. Recommendations include adopting comprehensive legal frameworks and promoting international cooperation to ensure ethical AI deployment aligned with human rights principles.